Pharmacokinetics and Pharmacodynamics of Azeloprazole Sodium, a Novel Proton Pump Inhibitor, in Healthy Japanese Volunteers. (28th November 2017) - Toda, Ryoko; Shiramoto, Masanari; Komai, Emi; Yoshii, Kazuyoshi; Hirayama, Masamichi; Kawabata, Yoshihiro
Abstract: The pharmacokinetics (PK) and pharmacodynamics (PD) of proton pump inhibitors differ among cytochrome P450 (CYP) 2C19 genotypes. Therefore, we developed azeloprazole sodium (Z‐215), a novel proton pump inhibitor, whose metabolism is not affected by CYP2C19 activity in vitro. However, the PK and PD of azeloprazole sodium have not been evaluated in Japanese subjects. We conducted an open‐label, crossover study in healthy Japanese male volunteers to evaluate the plasma concentration and intragastric pH with respect to CYP2C19 genotype after repeated administration of 10, 20, and 40 mg azeloprazole sodium and 10 and 20 mg rabeprazole sodium (rabeprazole). The plasma concentration profile of azeloprazole sodium was similar among genotypes, whereas that of rabeprazole differed. The 24‐hour intragastric pH ≥ 4 holding time ratio (pH ≥ 4 HTR) of azeloprazole sodium was similar among genotypes. The pH ≥ 4 HTR was 52.5%–60.3%, 55.1%–65.8%, and 69.4%–77.1% after administration of 10, 20, and 40 mg azeloprazole sodium, respectively, and 59.2%–72.3% and 64.4%–91.2% after administration of 10 and 20 mg rabeprazole, respectively, on the fifth day of dosing. The maximum plasma concentration (Cmax ), area under the plasma concentration‐time curve (AUC), and pH ≥ 4 HTR of azeloprazole sodium were proportional to dose. The Cmax, AUC, and pH ≥ 4 HTR on day 5 were slightly higher following administration of 20 mg azeloprazole sodium before comparison with after a meal. No serious adverse events were observed. These results suggest that azeloprazole sodium is useful for treating gastroesophageal reflux disease in all CYP2C19 genotypes.